Low CD4 Counts and History of Sore Throat Predict High SARS-CoV-2 Seropositivity among Human Immunodeficiency Virus-Infected Patients in Mwanza, Tanzania - Helmut A. Nyawale; Mariam M. Mirambo; Fabian Chacha; Nyambura Moremi; Mohamed Mohamed; Phares C. Lutema; Betrand Msemwa; James Samwel Mundamshimu; Bartholomeo Nicholaus; Stephen E. Mshana (COVID, 2023)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the ongoing coronavirus disease 2019 (COVID-19) pandemic. Despite the fact that it affects all ages and profiles, some evidence shows that patients with comorbidities, including diabetes, obesity, and hypertension, are likely to be most affected. For chronic diseases, such as human immunodeficiency virus (HIV), information is scarce, with a few studies from high-income countries. This study reports predictors of SARS-CoV-2 seropositivity (IgG + IgM) among unvaccinated people living with HIV attending Bugando Medical Centre in Mwanza, Tanzania. Methodology: A cross-sectional, hospital-based study involving 150 HIV-infected patients was conducted at Bugando Medical Centre between June and July 2022. A pretested questionnaire was used to collect the participants’ information. Blood samples were collected and used for the detection of SARS-CoV-2 (IgM/IgG) antibodies by immunochromatographic assay. Data were analyzed using STATA version 15. Results: The mean age of the enrolled participants was 46.4 ± 11.1 years. The overall seropositivity (IgG + IgM) of SARS-CoV-2 antibodies was 79/150 (52.7%) [95% CI: 44.4–60.9]. Seropositivity of IgM only was 8/150 (5.3) [95% CI: 1.7–8.8], while that of IgG only was 61/150 (40.6%) [95% CI: 32.7–48.4]. Seropositivity of both IgG and IgM was observed in 10/150 (6.7%) patients. In a multivariate logistic regression analysis, history of sore throat (OR: 6.34, 95% CI: 2.305–18.351, p < 0.001), low CD4 count (OR: 0.99, 95% CI: 0.995–0.999, p = 0.004), and use of pit latrines (OR: 2.30, 95% CI: 1.122–4.738, p = 0.023) were independently associated with SARS-CoV-2 seropositivity. Conclusion: HIV-infected individuals with history of sore throat, low CD4 count, and use of pit latrines were more likely to be SARS-CoV-2 IgG seropositive. There is a need to routinely screen for SARS-CoV-2 infection among HIV-infected individuals to obtain comprehensive data regarding the interactions of the pathogens.